Species diversity is a strong predictor of ecosystem multifunctionality under altered precipitation in desert steppes. (April 2022) - Hu, Ya; Li, Xiangyun; Guo, Aixia; Yue, Ping; Guo, Xinxin; Lv, Peng; Zhao, Shenglong; Zuo, Xiaoan
Graphical abstract: Highlights: Increased precipitation increases species, functional and phylogenetic diversity in the desert steppe. Ecosystem multifunctionality determined by eleven functions related to productivity and carbon and nitrogen cycle are increased by increased precipitation. Species, functional and phylogenetic diversity can explain ecosystem multifunctionality. Abstract: With the intensification of global climate change, the precipitation patterns are altered and grassland ecosystem is facing biodiversity loss and ecosystem services decline. It is of ecological significance to explore the underlying mechanisms of change in multiple ecosystem functions and services (multifunctionality) under altered precipitation. Plant community diversity (species, functional and phylogenetic diversity) has been proposed inducing links between ecosystem multifunctionality and environmental changes. However, which facet of plant community diversity can predict ecosystem function better remains controversial. Here, species, functional and phylogenetic diversity were investigated along precipitation gradients (−60%, −40%, −20%, CK, +20%, +40% and +60%) in the desert steppe of Inner Mongolia. In addition, ecosystem multifunctionality indices (averaging multifunctionality and threshold multifunctionality) were determined by eleven functions to assess the relationship between plant community diversity and multifunctionality under altered precipitation. We found that +40% and +60% precipitation significantly increased species richness by 52% and 33% and increased averaging multifunctionality by 20% and 46%. Functional and phylogenetic diversity at +60% precipitation were significantly higher than that at −60% treatment. Multifunctionality indices were positively correlated with precipitation gradients and plant community diversity. Importantly, species diversity possessed stronger predictive power of averaging multifunctionality than functional and phylogenetic diversity, which explained averaging multifunctionality of more than 38%. These results indicate that altered precipitation can change species composition of plant community and functions of ecosystem, further resulting in the closed relationship between species diversity and ecosystem multifunctionality. Our results highlight the critical role of species diversity in predicting multifunctionality of the altered precipitation conditions in desert steppes.